Teacher's Strategy in Improving Students' Ability to Memorize the Qur’an - Putri, Cyntia Tiara; Oktavia, Gifa; Syafura, Titi; Lainah, Lainah; Rahawarin, Yunus (International Journal of Multidisciplinary Research of Higher Education, 2021)
Memorizing the Qur’an is a noble act that is favored by Allah SWT. Because by memorizing the Qur’an it means we are trying to maintain the purity of the Qur’an. This cannot be separated from the efforts of a teacher in guiding his students to always memorize the Qur’an from an early age. It is the teacher's hard effort that determines the success of a student in memorizing the Qur’an. This study aims to analyze the strategy of tahfizh teachers in improving students' Qur’an memorization skills. This study uses a qualitative method with a phenomenological approach. The research subjects were teachers and students. Collecting data using the method of observation, interviews and documentation. All interview results were analyzed theoretically using techniques Analysis Interactive Model Miles & Huberman, namely data collection, data reduction, data presentation and drawing conclusions. The results of the data analysis found that there were six strategies carried out by the teacher in improving students' Qur’an memorization skills, namely; i) Using various methods, such as talaqqi, tasmi’ and takriri, ii) Applying the ODOA method (one day one ayat), iii) Guiding students to routinely Muraja’ah, iv) Always motivating students to improve their memorization of the Qur’an, v) Giving rote assignments and punishments to students, vi) The teacher corrects students' reading. The results of this study can be used as initial data for future researchers to examine this issue in different contexts and issues.